Anti-Inflammatory Effect of Deep-Sea Mineral Water on LPS-Induced Inflammation in Raw 264.7 Murine Macrophage Cells and Zebrafish Larvae - Hitihami M. S. M. Wijerathna; Bulumulle P. M. Vileka Jayamali; Deok-Soo Moon; Choong-Gon Kim; Sumi Jung; Jehee Lee (Immuno)
Deep-sea mineral water (DSW) consists of different compositions and properties. The composition can be varied in different seas all around the world. However, previous studies have investigated that DSW is a potential candidate that can be used to prevent different inflammatory diseases. Even though inflammation is an important protective mechanism in an animal, excessive inflammation causes organ failure and ultimate death. Therefore, the present study was carried out to investigate the anti-inflammatory effect of DSW extracted from the South Korean Sea to unveil its potential as an anti-inflammatory drug. To perform this, first, we have compared the cytotoxic effect of DSW on RAW 264.7 murine macrophage cells with NaCl and normal-sea water (NSW). Results reveal that DSW enhances cell survival while other treatments negatively affect cell survival. Furthermore, we have investigated that DSW reduces the LPS-induced cell apoptosis compared to the NaCl- and NSW-treated cells. Moreover, DSW has the ability to suppress the pro-inflammatory cytokine transcription (TNF-α, IL-1β, and IL-6) and NO production upon LPS treatment. In-vivo survival assay in zebrafish larvae shows a more than 50% survival rate in 10, 20, 30, 40, or 50% concentrations of DSW-treated larvae compared to NaCl- or NSW-treated larvae. Further investigations unveiled that DSW can negatively regulate the neutrophil and macrophage recruitment to the inflammatory site, which was induced by fin-fold amputation in zebrafish larvae and pro-inflammatory cytokine (tnf-α, il-1β, and il-6) secretion. Taken together, the present study concluded that DSW may have the ability to act as an anti-inflammatory drug to suppress excessive inflammation and subsequent consequences.